Linseed Oil Supplementation of Lambs’ Diet in Early Life Leads to Persistent Changes in Rumen Microbiome Structure - Lyons, Tamsin; Boland, Tommy; Storey, Sean; Doyle, Evelyn (Frontiers in Microbiology, 2017)
Diet has been shown to have a significant impact on microbial community composition in the rumen and could potentially be used to manipulate rumen microbiome structure to achieve specific outcomes. There is some evidence that a window may exist in early life, while the microbiome is being established, where manipulation through diet could lead to long-lasting results. The aim of this study was to test the hypothesis that dietary supplementation in early life will have an effect on rumen microbial composition that will persist even once supplementation is ceased. Twenty-seven new-born lambs were allocated to one of three dietary treatments; a control group receiving standard lamb meal, a group receiving lamb meal supplemented with 40 g kg-1 DM of linseed oil and a group receiving the supplement pre-weaning and standard lamb meal post weaning. The supplement had no effect on average daily feed intake or average daily weight gain of lambs. Bacterial and archaeal community composition was significantly (p = 0.033 and p = 0.005, respectively) different in lambs fed linseed oil throughout the study compared to lambs on the control diet. Succinivibrionaceae, succinate producers, and Veillonellaceae, propionate producers, were in a higher relative abundance in the lambs fed linseed oil while Ruminococcaceae, a family linked with high CH4 emitters, were in a higher relative abundance in the control group. The relative abundance of Methanibrevibacter was reduced in the lambs receiving linseed compared to those that didn’t. In contrast, the relative abundance of Methanosphaera was significantly higher in the animals receiving the supplement compared to animals receiving no supplement (40.82% and 26.67% respectively). Furthermore, lambs fed linseed oil only in the pre-weaning period had a bacterial community composition significantly (p = 0.015) different to that of the control group, though archaeal diversity and community structure did not differ. Again, Succinivibrionaceae and Veillonellaceae were in a higher relative abundance in the group fed linseed oil pre-weaning while Ruminococcaceae were in a higher relative abundance in the control group. This study shows that lambs fed the dietary supplement short-term had a rumen microbiome that remained altered even after supplementation had ceased.